The Effectiveness of Teacher Leadership and Students Involvement in Co-Curricular Activities in Malaysia Secondary School - Don, Yahya; Ibrahim, Ibrahim (IAIN Samarinda, 2019)
This paper aimed to identify the effectiveness of teacher leadership and student’s commitment with their involvement towards co-curricular activities in developing the soft skills among the Malaysian secondary school students. This study uses a quantitative approach in cross-sectional survey. The population of this study are the secondary school students from two states in Malaysia. The stratified random sampling is used to select 500 samples from the research population. The instruments used in this research are Organizational Commitment Qustionaire (OCQ) Mowday, Steers & Porter (1979), Leadership Practices Inventory (LPI) (Kouzes & Posner, 1995), and Soft Skills adopted by Razzaly Wahid et al. (2006). This result of this study shows that there is a significant and positive relationship between teacher’s leadership, student’s commitment and involvement with co-curricular activities, and student’s soft skills. Thus, the school leadership should play an important role in enhancing the invovement of the school co-curriculum activities to enhance the student’s soft skills. In addition, the school leadership should also look into the two important indicators which is the effectiveness of the leadership practice and the commitment of the students’s involvement as the outcome enshrined in the National Education Philosophy.